2020
DOI: 10.3390/ijerph17082736
|View full text |Cite
|
Sign up to set email alerts
|

Association between Working Hours and Self-Rated Health

Abstract: This study compared the association between working hours and self-rated health (SRH) according to sex, socioeconomic status, and working conditions. In all, 25,144 participants were selected from the Korea National Health and Nutrition Examination Survey (KNHANES), conducted from 2010 to 2018. The risks of poor SRH, according to working hours, were investigated using multiple logistic regression. Both short and long working hours were associated with poor SRH. Men working short hours and women working long ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Men and women spend time in short working hours for different reasons. It is well established that while majority of men spend time in short working hours for health reasons, majority of women spend time in short working hours to be able to combine paid work with childcare responsibilities ( 60 , 61 ). Thus, the present results that short working hours in paid work are associated with less-than-good SAH among men but not women, may be because men try to meet their paid work responsibility regardless of their health conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men and women spend time in short working hours for different reasons. It is well established that while majority of men spend time in short working hours for health reasons, majority of women spend time in short working hours to be able to combine paid work with childcare responsibilities ( 60 , 61 ). Thus, the present results that short working hours in paid work are associated with less-than-good SAH among men but not women, may be because men try to meet their paid work responsibility regardless of their health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present results that short working hours in paid work are associated with less-than-good SAH among men but not women, may be because men try to meet their paid work responsibility regardless of their health conditions. Few studies have demonstrated that unlike women with poor SAH, men with poor SAH may involuntarily engage in precarious jobs with short working time, and this in turn, may have adverse health outcome ( 61 ). Furthermore, the association between long working hours and less-than-good SAH among men may be attributed to work overloads, and prolonged work stress which is linked to poor health status ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Body mass index (BMI) was stratified into three groups: underweight (BMI<18.5 kg/m 2 ), normal (18.5 kg/m 2 ≤ BMI< 25 kg/m 2 ), and obese (BMI ≥ 25 kg/m 2 ) [13]. Working hours per week were classified into five groups: not working, < 20, 20-39, 40-59, and ≥ 60 [14]. Physical activity was defined as moderate-intensity physical activity for more than 150 minutes per week, high level of physical activity for more than 75 minutes, or a mix of moderate-and high-intensity physical activity [15].…”
Section: Covariatesmentioning
confidence: 99%
“… 18 19 In addition, high educational level, managerial and professional occupations, and precarious work schedules could affect the association between long working hours and poor SRH as moderating factors. 20 However, in most studies, income level has not been considered in depth. Therefore, this study aimed to investigate the relationship between working hours and SRH according to household income level using nationally representative population-based surveys in Korea.…”
Section: Introductionmentioning
confidence: 99%